Development of an anthropomorphic head phantom using dolomite and polymethyl methacrylate for dosimetry in computed tomography. (December 2015) - Ximenes, R.E.; Silva, A.; Balbino, D.; Poletti, M.E.; Maia, A.F.
Abstract: A real human skull was selected to be a mold for the construction of an anthropomorphic head phantom with a mixture of dolomite and polymethyl methacrylate (PMMA). Using linear attenuation coefficients, we show that it is possible to use dolomite as a bone simulator as long as the proportion of the mixture is 1:1. Acrylic tubes were placed in the phantom constructed to enable the insertion of the ionization chamber to estimate the effective dose. Values for a typical head computed tomography examination found in the literature vary from 0.9 to 4.0 mSv. Dosimetric studies showed that the effective dose for the anthropomorphic phantom was (2.70±0.03) mSv and for the geometric PMMA phantom (3.67±0.04) mSv, values which are in agreement with the intervals reported in the literature. The investment to produce the phantom was approximately US160.00. Highlights: A functional phantom using dolomite and PMMA was manufactured for US160.00. Dolomite in a 1:1 mass proportion with PMMA is a bone substitute in CT exams. Dosimetric studies showed that PMMA phantom overestimates the dose of the patient.